2017
DOI: 10.4172/1745-7580.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 as a Target for Immunomodulation Strategy in Inflammatory Bowel Diseases

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory pathologies of the gut, characterized by a relapsingremitting course. Although IBD pathogenesis is not fully understood, epidemiological and experimental data suggest that multiple environmental factors can, in genetically predisposed individuals, trigger an excessive immune response directed against the antigens of the normal intestinal microflora, which eventually leads to the tissue damage. Defects in the physiological mechanisms/factors of counter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Smad7 inflammatory role in immune‐mediated inflammatory diseases can be confirmed by reviewing previous studies. Sedda et al 26 demonstrated the inflammatory role of Smad7 in inflammatory bowel disease. In addition, they support the concept that knockdown of Smad7 with Mongersen as targeted therapy can be a promising therapeutic approach to modulate the ongoing mucosal inflammation in inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Smad7 inflammatory role in immune‐mediated inflammatory diseases can be confirmed by reviewing previous studies. Sedda et al 26 demonstrated the inflammatory role of Smad7 in inflammatory bowel disease. In addition, they support the concept that knockdown of Smad7 with Mongersen as targeted therapy can be a promising therapeutic approach to modulate the ongoing mucosal inflammation in inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%